Independent validation of the ICU requirement score in a cohort of acutely poisoned adults. (3rd July 2018) - Böll, Regina; Romanek, Katrin; Schmoll, Sabrina; Stich, Raphael; Ott, Armin; Stenzel, Jochen; Geith, Stefanie; Eyer, Florian; Rabe, Christian
Abstract: Objective: To independently validate the predictive value of the intensive care requirement score (IRS) in unselected poisoned patients. Design: Retrospective chart review. Patients and methods: Five hundred and seventeen out of 585 admissions for acute intoxications could be analyzed. Eleven were excluded for a condition already requiring intensive care unit (ICU) support at admission (e.g., preclinical intubation). A further 57 admissions were excluded due to missing data. The IRS was calculated using a point-scoring system including age, Glasgow Coma Scale, heart rate, type of intoxication, and preexisting conditions. It was then compared to a composite endpoint indicating an ICU requirement (death in hospital, vasopressors, need for ventilation). The endpoint and the point-scoring system were identical to the original publication of the score. Results and conclusion: Twenty-three out of 517 patients had a complicated clinical course as defined by meeting the endpoint definition. Twenty-one out of 23 complicated courses had a positive IRS (defined as greater or equal 6 points), as compared to 255/494 patients with an uncomplicated clinical course ( p  < .001, Fisher's exact test). One patient (with a positive IRS) died. The negative predictive value of the IRS was 0.99 (95% CI: 0.97–1), the sensitivity was 0.91 and the specificity 0.48. In conclusion, the IRS is significantly linked to outcome. While a negative IRS virtually excludes the need for ICU care, a positive IRS has a positive predictive value too low to be used for risk stratification. The IRS could also be applied to unselected admissions of poisoned patients.